Pragmatic ellipsis and its pragmatic consequences: Chinese ’ye shi’ at the syntax-pragmatics interface - Chen, Yifan; Hu, Xuhui (East Asian Pragmatics, 2024)
This article focuses on the chunk ye shi (literally “also be”) in Chinese. Ye is a contrastive focus marker, yet in some ye shi sentences, there is no overt alternative for contrast. Besides, these sentences carry specific pragmatic implicatures. We propose that these sentences do not form a challenge to ye’s status as a contrastive focus marker. Ye has two core properties: (1) it presupposes the existence of alternatives to contrast with the focus it marks; (2) it implicates a sense of counter-expectation when marking the focus. These two properties can account for all uses of ye shi, including their specific implicatures. Moreover, these two properties are assumed to be shared by ye-type contrastive focus markers cross-linguistically. The alternative evoked by ye shi can be elided through a mechanism named by us as pragmatic ellipsis. It differs from the traditional syntactic ellipsis. The way how ye shi obtains the pragmatic ellipsis use reflects a syntax-to-pragmatics way of grammaticalisation, challenging the unidirectionality hypothesis proposed by Hopper and Traugott (1993).